Concomitant Use of Selective Serotonin Reuptake Inhibitors and Oral Anticoagulants and Risk of Major Bleeding: A Systematic Review and Meta-analysis - Rahman, Alvi A.; He, Na; Rej, Soham; Platt, Robert W.; Renoux, Christel (Thrombosis and Haemostasis, 2022)
Background Selective serotonin reuptake inhibitors (SSRIs), the most prescribed antidepressants, are associated with a modestly increased risk of major bleeding. However, in patients treated with both SSRIs and oral anticoagulants (OACs), the risk of major bleeding may be substantial.Objective To assess the risk of major bleeding associated with concomitant use of SSRIs and OACs, compared with OAC use alone.Methods We searched MEDLINE, Embase, PsycINFO, and the Cochrane Central Register of Controlled Trials (from inception to December 1, 2021) for clinical trials and observational studies assessing the association between concomitant use of SSRIs and OACs and the risk of major bleeding. Given sufficient homogeneity of studies, we conducted a random-effects meta-analysis to estimate a pooled hazard ratio (HR) of major bleeding associated with concomitant use of SSRIs and OACs, compared with OAC use alone.Results The review comprised 14 studies, including 7 cohort and 7 nested case–control studies. Following assessment of clinical and methodological heterogeneity, eight studies with a total of 98,070 patients were eligible for the meta-analysis. The pooled HR of major bleeding associated with concomitant use of SSRIs and OACs was 1.35 (95% confidence interval [CI]: 1.14–1.58). In secondary analyses, the pooled HR for concomitant use of SSRIs and direct OACs was 1.47 (95% CI: 1.03–2.10).Conclusion Concomitant use of SSRIs and OACs was associated with an increased risk of major bleeding. Overall, our findings suggest that physicians may need to tailor treatment according to individual patient risk factors for bleeding when prescribing SSRIs to patients using OACs.
Keywords: clinical trial; anticoagulation; inhibitors; hemostasis